(untitled) (Revista de História Regional, 2022)
This article aims to understand memory, through the use of the Oral History technique, as a fundamental part in the construction of a regional historiographical process. For this, it was necessary to detail the concept of memory very extensively, understanding it as individual memories in charge of building a collective memory, an observation that results from an important state of the art that mapped an extensive bibliographical research already developed on the subject and empirical work carried out on the subject. from the use of a series of oral interviews conducted by myself and others arranged in public and private collections with a group of people involved in the fight against the Brazilian military dictatorship. In addition, this work seeks to demonstrate the need for new scientific approaches for the knowledge and recognition of actions that occurred far from the country’s large urban centers, such as Rio de Janeiro and São Paulo, but locally and regionally on historical moments of national relevance and in the field of the History of the Present Time, as in the case of human rights violations committed by the military in the period between 1964 and 1985, for example. As Le Goff thought, there is a writing of history and this work aims to demonstrate that Oral History allows us to rescue this way of conceiving historiography.